2002
DOI: 10.1046/j.1460-9568.2002.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of norepinephrine decreases the proliferation, but does not influence the survival and differentiation, of granule cell progenitors in the adult rat hippocampus

Abstract: The dentate gyrus region retains the ability to generate neurons throughout adulthood. A few studies have examined the neurotransmitter regulation of adult hippocampal neurogenesis and have shown that this process is regulated by serotonin and glutamate. Given the strong noradrenergic innervation of the adult hippocampus and the ability of norepinephrine to influence proliferation during development, we examined the influence of norepinephrine on adult hippocampal neurogenesis. Our study indicates that depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
2
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 19 publications
9
101
2
5
Order By: Relevance
“…Antidepressant treatment increased neuronal progenitor-cell proliferation to a similar degree in both wild-type mice and in two transgenic strains of mice with reduced BDNF signaling, trkB.T1-overexpressing mice and BDNF ϩ/Ϫ mice. These data indicate that the proliferation phase is not regulated by neurotrophins but is regulated by other effects, most likely involving the increase in extracellular levels of serotonin and norepinephrine (Gould, 1999;Kulkarni et al, 2002;Santarelli et al, 2003). In contrast, our data suggest that the longterm survival on the newly born neurons appears to require functional BDNF signaling (Lee et al, 2002), as has also been reported in vitro (Barnabe-Heider and Miller, 2003).…”
Section: Discussionsupporting
confidence: 67%
“…Antidepressant treatment increased neuronal progenitor-cell proliferation to a similar degree in both wild-type mice and in two transgenic strains of mice with reduced BDNF signaling, trkB.T1-overexpressing mice and BDNF ϩ/Ϫ mice. These data indicate that the proliferation phase is not regulated by neurotrophins but is regulated by other effects, most likely involving the increase in extracellular levels of serotonin and norepinephrine (Gould, 1999;Kulkarni et al, 2002;Santarelli et al, 2003). In contrast, our data suggest that the longterm survival on the newly born neurons appears to require functional BDNF signaling (Lee et al, 2002), as has also been reported in vitro (Barnabe-Heider and Miller, 2003).…”
Section: Discussionsupporting
confidence: 67%
“…[81][82][83] Additionally, persistent elevation of circulating corticosteroids can also cause atrophy of other important brain regions for cognitive and emotional processes, such as the prefrontal cortex and amygdala. [84,85] As depletion of central NE leads to a decline in adult hippocampal neurogenesis, [86,87] it is likely that an elevation of NE (e.g., by antidepressants) has an indirect role in regulating BDNF-dependent adult hippocampal neurogenesis. [88] This elevation of BDNF may be an important part of the cellular processes that underlie antidepressant efficacy.…”
Section: Stress Ne Brain-derived Neurotrophic Factor and Adult Neurmentioning
confidence: 99%
“…Wood et al, 2001;Berg et al, 2006;Dekeyne et al, 2008;Chanrion et al, 2008;Millan MJ unpublished observations). The notion that inverse agonism is required for enhancing proliferation in the VH is supported by evidence that certain cerebral populations of 5-HT 2C receptors are constitutively active (Berg et al, 2005), including sites tonically inhibitory, through GABAergic interneurones, to ascending dopaminergic or noradrenergic systems that are known to increase cell proliferation (Invernizzi et al, 2007;Hoglinger et al, 2004;Kulkarni et al, 2002;Millan et al, 2008;Aloyo et al, 2009). However, the interpretation of these data is also complicated by the fact that constitutive activity at 5-HT 2C sites is regulated by mRNA editing that differs between brain regions; extensively edited 5-HT 2C receptor isoforms being constitutively silent (Burns et al, 1997;Sanders-Bush et al, 2003).…”
Section: Figurementioning
confidence: 99%